Transient hyperthyroidism after surgery for secondary hyperparathyroidism: a common problem - Rudofsky, Gottfried; Tsioga, M.; Reismann, P.; Leowardi-Bauer, Christine; Kopf, Stefan; Grafe, Ingo Alexander; Nawroth, Peter Paul; Isermann, Berend (European journal of medical research, 2011)
Postoperative hyperthyroidism occurs in approximately one third of patients following parathyroidectomy due to primary hyperparathyroidism (PHP), but has only rarely been described in secondary hyperparathyroidism (SHP). The frequency, course, and laboratory markers of postoperative hyperthyroidism in SHP remain unknown. Our purpose was to evaluate the frequency and the clinical course of postoperative hypcrthyroidism following surgery of SHP and to determine the diagnostic value of thyroglobulin in this setting.
Gesehen am 21.09.2022